Boundary layer development over non-uniform sand rough bed channel. Issue 2 (4th May 2019) - Sharma, Anurag; Kumar, Bimlesh
Abstract: Experimental investigations were carried out to investigate the development of boundary layer in non-uniform sand bed channels with and without seepage. Steady flows over non-uniform sand bed channel were simulated experimentally with downward seepage applied through the boundary. Velocity measurements were made at 12 different sections along the channel mid-section for no seepage and seepage flow conditions to investigate the fully developed flow condition. High boundary layer thickness and small boundary layer development length are observed for no seepage runs as compared to seepage runs. The value of boundary layer development length varies between 56 and 65 times of the flow depth for all flow conditions. The present study develops empirical equations to predict boundary layer thickness and flow development length in seepage affected alluvial channel under present experimental conditions.